DESIGN OF GUIDANCE AND COUNSELING PROGRAMS TO IMPROVE SOCIAL SKILLS OF ELEMENTARY SCHOOL STUDENTS - Fikriyah; Vani Setyaningsih; Hanikah; Muhammad Nana Suryana (Jurnal Abdisci, 2024)
This study aims to develop a guidance and counseling program at SDN 1 Kenanga Kec. Sumber to improve students' social skills. The background of this study stems from the growing concern about students' social skills in primary schools, particularly in SDN 1 Kenanga sub-district Sumber. Initial evaluations and observations revealed that many students in the school were lacking in essential social skills such as communication, cooperation and conflict resolution. These imperfections can have a significant impact on students' ability to succeed academically and socially, both in and out of school. This study used qualitative research methods to create an effective program for guidance and counseling services that can be implemented at SDN 1 Kenanga sub-district Sumber, with the ultimate goal of improving students' social skills. The main objective of this research is to design the development of an effective guidance and counseling service program. The results of this program design are the development of a service program that includes network development, development of guidance and counseling management activities, service development, and development of service types as well as design and action plans that include identification, time management, inventory of needs and types of services, implementation, reflection, and program evaluation. This program is expected to improve students' social skills at SDN 1 Kenanga sub-district Sumber.